Identical Genes, Unique Environments: A Qualitative Exploration of Persistent Monozygotic-Twin Discordance in Literacy and Numeracy - Larsen, Sally A.; Byrne, Brian; Little, Callie W.; Coventry, William L.; Ho, Connie S.; Olson, Richard K.; Stevenson, Annette (Frontiers in Education, 2019)
This study aimed to explore unique environmental factors impacting differential academic trajectories among Australian school students. Monozygotic (MZ) twin pairs who were consistently discordant in results of nationwide standardized tests of reading, numeracy or writing between Grades 3 and 9 were identified. MZ twins control for genes, gender, age and aspects of the home and school environment shared by twins. Thus any difference between MZ twins in academic outcomes can be attributed to the unique environment experienced by each twin. From 551 MZ twin pairs with three or four sets of test results, we identified 55 pairs who were substantially and consistently discordant in reading, numeracy or writing between Grades 3 and 9. Parents were contacted for interview, resulting in 40 semi-structured interviews. Qualitative data analysis revealed three major themes, interpreted by parents as possible contributors to persistent academic discordance: biological mechanisms, school-based factors and personal factors. We discuss implications for educational practice, policy and research.